2011
DOI: 10.1186/1471-230x-11-10
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Sterol Carrier Protein 2 in Patients with Hereditary Cholesterol Gallstones

Abstract: BackgroundLithogenic bile is the major cause of cholesterol gallstone, but its pathogenesis is not well understood. The hypersecretion of biliary cholesterol is believed to be an important cause of lithogenic bile. Sterol Carrier Protein 2 (SCP2) participates in cholesterol trafficking and lipid metabolism in hepatocytes and may play a key role in cholesterol gallstone formation.Methods21 cholesterol gallstone genealogies were studied to investigate the expression of SCP2 gene in liver tissue of hereditary and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…In rodents, SCP2 gene expression manipulation has shown that hepatic SCP2 regulates biliary cholesterol rather than biliary phospholipid and bile salt secretion (62–64). Consistent with these findings, increased hepatic SCP2 expression levels were detected in mice with a genetic predisposition to gallstone disease due to biliary cholesterol hypersecretion (65) and in patients with gallstones (66, 67). However, SCP2 deficiency did not prevent gallstone formation in mice fed with a lithogenic diet (68), suggesting that the role of SCP2 is not critical for gallstone formation.…”
Section: Intrahepatic Cholesterol Traffickingsupporting
confidence: 63%
“…In rodents, SCP2 gene expression manipulation has shown that hepatic SCP2 regulates biliary cholesterol rather than biliary phospholipid and bile salt secretion (62–64). Consistent with these findings, increased hepatic SCP2 expression levels were detected in mice with a genetic predisposition to gallstone disease due to biliary cholesterol hypersecretion (65) and in patients with gallstones (66, 67). However, SCP2 deficiency did not prevent gallstone formation in mice fed with a lithogenic diet (68), suggesting that the role of SCP2 is not critical for gallstone formation.…”
Section: Intrahepatic Cholesterol Traffickingsupporting
confidence: 63%
“…Additionally, some researchers indicate that it may have a role in the biosynthesis of cholesterol, (11)(12)(13) and in the transformation of cholesterol to bile acids (14,15), cholesterol esters (16) and sterols (17). Our former findings indicated that SCP2 was overexpressed in patients with hereditary cholesterol gallstones when compared to patients with non-hereditary cholesterol gallstones, and that SCP2 may be a potential genetic factor that contributes to the formation of cholesterol gallstones (18). Hence, the hypersecretion of biliary cholesterol and formation of lithogenic bile may explain the mechanism of cholesterol stone formation in the gallbladder.…”
Section: Introductionmentioning
confidence: 81%
“…The significant growth in colonoscopies nationwide since 1995 suggests that colonoscopy is being used as a primary screening and surveillance tool [30], instead of iFOBTs as the Australian National Health & Medical Research Council (NHMRC) guidelines recommend. An alternative approach to invasive modes of CRC screening is supported by recent evidence from a systematic review [31] and modeling of CRC symptoms [32]. These studies identified population subgroups at higher risk of CRC, with increasing age, rectal bleeding and weight loss being the most accurate predictors of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…These studies identified population subgroups at higher risk of CRC, with increasing age, rectal bleeding and weight loss being the most accurate predictors of CRC. The systematic review concluded that, given the current evidence, “it seems wise to channel resources for cancer detection towards population based screening programs using FOBT rather than relying on identifying all cancers and precancerous polyps through investigating people with symptoms” [31]. Focusing on FOBT as the primary screening test can avoid unnecessary and wasteful use of resources that could then be redirected to other areas of the program.…”
Section: Discussionmentioning
confidence: 99%